FAKTOR-FAKTOR YANG MENYEBABKAN KETERLAMBATAN WAKTU PELAKSANAAN PROYEK PADA PEKERJAAN JALAN DAN JEMBATAN DI KABUPATEN MOROWALI - Elce Misba Bansambua (Fakultas Teknik Universitas Sintuwu Maroso, 2013)
This research was conducted in Morowali Regent the methodology used in this research was library research to find out the causes of the delay, at the government project implementation such as roads, bridges, dams and buildings at the financial year 2011 using index value calculation analysis. The results show that factors of the delay causes of the roads, bridges, dam and buildings implementation projects were the insufficient of suitable building materials in accordance the needs (D4) with index value 96.67 and the delay mobility resources (materials, instruments, human power) (D1) was with index value 93.33